Onshore sandbar migration in the surf zone: New insights into the wave‐induced sediment transport mechanisms. Issue 8 (17th April 2015) - Fernández‐Mora, A.; Calvete, D.; Falqués, A.; de Swart, H. E.
Abstract We present a novel process‐based morphodynamic model, which includes transport processes due to both velocity and acceleration skewness and a new formulation for intrawave motions, that successfully simulates observations of onshore sandbar migration. Results confirm findings of previous studies, in which each process was considered separately and in which sediment transport was computed from the observed water motion. However, our results indicate that accounting for the joint action of both velocity and acceleration skewnesses causes major improvement of the modeled onshore bar migration and is essential to accurately model the evolution of the entire cross‐shore bottom profile, when compared with observations. We also demonstrate that the morphodynamics in the shoaling zone are dominated by velocity skewness (bed shear stresses), while sediment transport induced by acceleration skewness (pressure gradients) controls the morphodynamics in the inner surf zone.